2018
DOI: 10.1007/s12369-018-0490-7
|View full text |Cite
|
Sign up to set email alerts
|

The Background Context Condition for the Uncanny Valley Hypothesis

Abstract: We present the results of the background context condition experiment for the uncanny valley hypothesis. Subjects were presented with 12 computer-generated 3D models in two background variants. For the first group 12 models were rendered on a neutral background (empty room) and for the second group the same models were rendered on a suitable background, which was relevant to a given model (science-fiction scenery, town etc.). The aim of this study was to check whether the background context would influence dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…It is worth to mention here that when it comes to human-likeness assessment of models from our study sample we have obtained analogical results to the ones from the study presented in [7]. What is more, the same set of models was used in another study concerning the background condition for UVH (see [8])-also in this case the DOH ordering was the same (four groups of models were established by subjects' evaluations). This suggests that the set of models prepared for aforementioned studies provides a good and already tested starting point for future modifications and research (see the internal validity discussion for UVH related research in [6]).…”
Section: Summary and Discussionsupporting
confidence: 67%
“…It is worth to mention here that when it comes to human-likeness assessment of models from our study sample we have obtained analogical results to the ones from the study presented in [7]. What is more, the same set of models was used in another study concerning the background condition for UVH (see [8])-also in this case the DOH ordering was the same (four groups of models were established by subjects' evaluations). This suggests that the set of models prepared for aforementioned studies provides a good and already tested starting point for future modifications and research (see the internal validity discussion for UVH related research in [6]).…”
Section: Summary and Discussionsupporting
confidence: 67%
“…Furthermore, the generality of warmth items makes them susceptible to confounds. Stimulus evaluation could be influenced by, for example, background, clothing, color, narrative and framing, verbal and nonverbal behavior, interactivity, personality, relationships, and culture [Brink et al 2019;Kennedy 2014;Łupkowski et al 2018;MacDorman 2019;]. Thus, warmth items do not indicate the UV effect but a related construct.…”
Section: Other Constructs Other Constructs and Their Associated Measures And Theories Includementioning
confidence: 99%
“…Nevertheless, it has been shown that the realism of inanimate objects does not cause the uncanny valley effect (MacDorman et al, 2009). Additionally, Łupkowski, Rybka, Dziedzic, & Włodarczyk (2018) showed that background context is not an important factor for the uncanny valley. For that reason, it is important for game designers to focus on the creation of characters in high realism environments.…”
Section: Still Uncannymentioning
confidence: 99%